We Are All Monsters: How Deviant Organisms Came to Define Us, by Andrew Mangham - İpekçi, Yeşim (My University, 2024)
Andrew Mangham’s monograph entitled We Are All Monsters: How Deviant Organisms Came to Define Us (2023, The MIT Press) explores the polyvocal nature of monster science across the period 1750-1900 and its dialogue with nineteenth-century literature. Mangham’s “monsters,” as defined in biological sciences, are “organisms … born with at least one permanent physiological defect” (p. 1). Guided by the approach disability studies takes towards the term “disability,” he explores how monster science defines monstrosity “not as a failure, but as an embodiment of, or a cog in the machine of, organic law” (p. 2). Monsters with their corporeal singularities and differences are integral to the laws of nature. They are not “by-products of the laws of natural development which they had failed in varying ways to embody,” but “the adaptive workings and the dynamic forces to which all life forms, normal and abnormal, owe their being” (p. 2). In other words, congenital anomalies or corporeal deviations are structural variations which are not the antithesis of what is “normal” or “natural,” but significations of life’s variety and the ingenuities of nature. Mangham’s choice of literary works from the long nineteenth century helps explore the interplay between monster science and literary or imaginary monsters, emphasizing how they represent monstrosity as central to the interpretation of nature’s diversity and creativity. Offering an in-depth survey of monster science across the period and its literary reverberations in nineteenth-century novels, We Are All Monsters interrogates the causes and meanings of monstrosities with the claim that congenital structural deformities or differences are not failures or violations of nature’s laws, but symbols of vital creativity. With this claim at the center of his work, Mangham explores how Mary Shelley’s Frankenstein (1818), Charles Dickens’s The Old Curiosity Shop (1840-1841), and Lucas Malet’s The History of Sir Richard Calmady (1901) engage in dialogue with the ideas developed in monster science and problematize the meanings of difference and normalcy.
Keywords: Wilkie Collins; Andrew Mangham; We Are All Monsters: How Deviant Organisms Came to Define Us; monster science; nineteenth-centuryliterature